Change from sixfold to fivefold coordination of silicate polyhedra: Insights from first-principles calculations of CaSi2O5 - Warren, M; Redfern, S; Angel, R (1999)
Recent x-ray-diffraction observations found a triclinic phase of CaSi2O5 stable under ambient conditions, related to a monoclinic phase with the titanite structure. It differs from the titanite structure by the elongation and loss of a Si-O bond within a SiO6 octahedron, thus having SiO5 polyhedra. We have studied both these phases using density-functional theory in the generalized gradients approximation, to investigate the relative stability and chemical changes between the phases. Mulliken analysis is used to calculate covalent bond populations and atomic charges. A series of intermediate structures are studied to approximate a prototype transition pathway. ©1999 The American Physical Society.